Information Security Compliance Framework For Data Center In Utility Company - Yuvaraaj Velayutham; Ganthan Narayana Samy; Nurazean Maarop; Noor Hafizah Hassan; Wan Haslina Hassan; Sivakumar Pertheban; Sundresan A/L Perumal (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2024)
Non-Indexed Publication